Taking Stock of Temporary Organizational Forms: A Systematic Review and Research Agenda - Bakker, René M. (International journal of management reviews : IJMR, 2010)
This paper brings together the research on temporary organizational forms. Despite a recent surge in publications on this topic, there have been few attempts to integrate knowledge on what we know of such temporary forms of organization. In order to correct this, an integrative framework is proposed around four central themes: time, team, task and context. Within each of these themes, the paper offers an overview of the literature, the gaps in what we know, and what future directions might be taken by scholars hoping to contribute to this important and rapidly growing field.